High-Voltage MOSFET-Based Stacked RF Switch with Extended Bandwidth Down to DC - Syroiezhin, Semen; Weigel, Robert; Solomko, Valentyn (IEEE Solid-State Circuits Letters, 2023)
State-of-art stacked MOSFET-based RF switches cannot handle DC voltages exceeding maximum ratings of individual transistors in stack. In this paper a shunt switch constructed from stacked low-voltage transistors and capable of handling high DC and AC voltages in OFF-state is demonstrated for the first time. The DC voltage handling capability is achieved by introducing a resistive gate bias network coupled to the poles of the switch. An analytical model of the bias network is presented in the paper. A hardware prototype of the proposed device has been implemented in a dedicated 65 nm RF-switch SOI-CMOS process. The measurements of a 20-stack switch demonstrated peak RF and DC voltage handling of 20 V with the potential for further improvement and state-of-art linearity.
CRIS-Team Scopus Importer:2023-05-05
Keywords: Actuators; CMOS switch; high-voltage switch; linear switch; Logic gates; Radio frequency; stacked switch; Switches; Switching circuits; Transistors; tunable devices; Voltage control; Voltage measurement